Visceral artery aneurysms - review - Żyga, Justyna; Wysokińska, Olga; Małek, Anna; Zadrożna, Karolina; Iwaniszyn-Zapołoch, Klara (Journal of Education, Health and Sport, 2022)
Introduction: Visceral artery aneurysms remain a rare condition. A rupture is the dangerous complication, which occurs in about 10-20% of the cases, they have a high mortality rate estimated up to 70%. Rupture percentage is higher in pregnancy, up to 50%, with considerable mortality rates of 75% for the pregnant and 95% for the foetus. The most common location of abdominal aneurysm is splenic artery with prevalence of 60% out of visceral aneurysms affecting this vessel. Since they are asymptomatic in 95% of cases, they are usually a random finding of examinations performed for other indications. State of knowledge: Patients with a suspected visceral aneurysm are qualified for ultrasound as the first line examination, but currently computed tomography is the most favourable method. Catheter-based angiography is considered to be the gold standard. It allows precise identification of the location of aneurysm and its morphology. For the treatment of visceral artery aneurysms numerous ways are available, however the endovascular method is recommended as the first choice in most cases. Conclusions: Visceral artery aneurysms are a rare but potentially fatal pathology. The silent nature makes it difficult to diagnose. When recognised, aneurysms should be treated immediately, since rupture is associated with a considerable high mortality rate. Open and endovascular interventions are equally durable for elective repair of visceral artery aneurysms, but endovascular interventions are considered to be safe and effective, resulting in lower morbidity and mortality rate. There is a need for further large studies evaluating effectiveness and long-term outcome of endovascular treatment.